The Impact of Forced Displacement on Host Communities. A Review of the Empirical Literature in Economics - Paolo Verme; Kirsten Schuettler (Global Labor Organization (GLO), 2020)
The paper reviews the literature that estimated the impact of forced displacement on host communities. A comparative analysis of the empirical models used in 59 studies and a meta-analysis of 972 results collected from these studies are the main contributions of the paper. Coverage extends to 19 major forced displacement crises that occurred between 1922 and 2018, high, medium and low-income host countries and different types of forced migrants. Results refer to outcomes related to employment, wages, prices and household well-being. The meta-analysis finds that most results on employment and wages are non-significant. When significant, decreases in employment and wages are more likely to occur than increases with decreases strongly associated with the short-term, middle-income countries, females, young and informal workers. Food and rent prices tend to increase in the short-term. The probability of observing a decrease in household well-being among hosts is lower than 1 in 5.
Keywords: D12; E24; F22; F66; J08; J1; J2; J3; J4; J7; J8; N3; O15; P46; R2; 330; Refugees; Returnees; Expellees; Escapees; Internally Displaced Persons (IDPs); Forced Migration; Forced Displacement; Host Communities; Labor Markets; Wages; Prices; Employment; Unemployment; Well-being